Implementación de un Sistema de Seguimiento Automático de Satélites Pequeños para la recepción e Interpretación de Señales Beacon desde la Estación Terrena del CTIC-UNI - Inga y Cols., Dante (2019)
In recent decades, universities and technology institutes have joined the construction of artificial satellites; they are developing small satellites for research in aerospace. These satellites require at least one ground station, which uses hardware and software to establish communication with the satellite. In addition, ground stations have computerized systems to manage data from the satellite. This document describes the procedures for automatic tracking of small satellites to receive Beacon signals, i.e. basic information that are sent by small satellites on a regular basis in the form of radio-frequency signals. The system uses a set of hardware devices such as radio, antenna, rotor, TNC, which will be responsible for receiving satellite data, the system also uses software for remote management of equipment and data received. Small satellites are usually low orbit, i.e., they are orbiting around the earth at an altitude of between 200Km and 800Km, moving at high speeds relative to ground station. Therefore, the position of the satellite transmitter and the frequency of the received signal changes continuously, then antenna orientation and radio frequency adjustment are required, these often are done manually. Automatic control of radio frequency and antenna orientation improves the reception of Beacon signals emitted by the satellite. The frequency shift and antenna angle values are obtained by orbit predictor software and equipment will be handled by open-source libraries; also, using the advantages of the internet, we can control the system from any PC with Internet access. The main objective is to improve the reception of satellite signals, reduce noise level, facilitate earth station monitoring and get automatic decoding with few errors. The information obtained through Beacon signal is coded using Morse code, which is why it is necessary to use a TNC to decode the information. The management software for small satellite data obtained is based on Mercury project, adapted to the hardware of CTIC-UNI ground station. We achieved on-line decoding of Beacon signals from several small satellites that are operational to date.